Parallel Edge-Based Inexact Newton Solution of Steady Incompressible 3D Navier-Stokes Equations - Elias, Renato N.; Martins, Marcos A. D.; Coutinho, Alvaro L. G. A. (Euro-Par 2005 Parallel Processing, 2005)
The parallel edge-based solution of 3D incompressible Navier-Stokes equations is presented. The governing partial differential equations are discretized using the SUPG/PSPG stabilized finite element method [5] on unstructured grids. The resulting fully coupled nonlinear system of equations is solved by the inexact Newton-Krylov method [1]. Matrix-vector products within GMRES are computed edge-by-edge, diminishing flop counts and memory requirements. The non-linear solver parallel implementation is based in message passing interface (MPI). Performance tests on several computers, such as the SGI Altix, the Cray XD1 and a mini-wireless cluster were carried out in representative problems and results have shown that edge-based schemes require less CPU time and memory than element-based solutions.